An idea of thin-plate thermal mirror. II. Mirror created by a constant heat flux - Płochocki, Z.; Mioduchowski, A. (Archives of Mechanics, 1998)
Following Part I, an idea of thermal mirrors created on the surfaces of a simply supported thin plane circular plate of an isotropic thermoelastic solid material by a uniform constant beat flux, which is applied to one of the plate surfaces, is presented. Such a thermal mirror is - within the approximations applied for obtaining the solutions of the heat conduction and thermoelasticity equations - an ideal (aberration-free) optical mirror. The optical properties of the thermal mirror and their time evolution are derived in two extreme cases: a) no energy losses through both plate surfaces, and b) no losses through the perturbed surface and the maximum losses through the opposite surface, and discussed in two asymptotical regimes: the short-time and the long-time ones. Theoretical possibilities of application of the thermal mirror to experimental determination of temperature conductivity of a material are discussed.